The future in Greek from ancient to medieval - Markopoulos, Theodore; Oxford eBooks (Oxford : Oxford University Press, 2009)
This text on the history of Greek explores what led to the appearance of the modern future in the 16th century. The author traces its origins to the classical period and its development in the Hellenistic. He shows how his findings affect the Greek syntactic and semantic history and grammaticalization theory in general.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Greek language -- History; Greek language -- Tense -- History; Greek language, Hellenistic (300 B.C.-600 A.D.) -- Tense; Greek language, Medieval and late -- Tense; Electronic books